LOGIC METHODS OF EXPRESSION IN HUMANITARIAN KNOWLEDGE - Yurkevych, Olena M. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2019)
Purpose: finding out the features of logical methods for obtaining conclusions on humanitarian subjects. The task of this scientific research is to analyze the logical paradigmatic aspects of humanitarian knowledge, such as the differences in the formation of sets, logical forms and conclusions, and so on. Methods: a set of logical methods such as analysis, synthesis, abstraction and generalization, informal logic of understanding, etc. Scientific novelty: the logic of humanitarian knowledge is formed on the basis of the logic of historical knowledge, the specificity of which is manifested in the special meaning of individual sets that receive direct and indirect meaning, form the corresponding logical connections in obtaining conclusions. When obtaining conclusions on humanitarian subjects, the formation of an exemplary individual is a plurality. Its ideal qualities are transferred to an unnamed set. Thus, the integrity of the humanitarian subject is created. In the transition from parts to the whole there is a “logical jump”, which is also the difference in the procedure for obtaining a conclusion. Widely used rational understanding by identifying the value of the whole. Understanding can be strong or weak. The difference in the logic of humanitarian knowledge is primarily due to the peculiarity of the work of human thinking, which uses specific tools in formatting various scientific disciplines and organizing the cognitive process. Among the many new approaches and methods of the humanities developed in phenomenology, existentialism, philosophy of life, structuralism, postmodernism, etc., hermeneutics should be noted. It is hermeneutics that occupies a special place in humanitarian knowledge due to its ontology and logic. Conclusions: the logic of humanitarian knowledge is formed on the basis of historical consciousness, relies on ontology and has signs of the logic of practical thinking. In its formation, it is advisable to use the theory of practical judgments and conclusions, taking into account subjective values of life experience, obtaining the logical values of truth and falsehood. The terms of deductive and non-deductive forms are based on judgments about values. The logic of humanitarian knowledge to a large extent is hermeneutical logic, which, in turn, is the logic of rational understanding.